3D-printed Cutting Guides for Lower Limb Deformity Correction in the Young Population. Issue 5 (24th May 2022) - Gigi, Roy; Gortzak, Yair; Barriga Moreno, Juan; Golden, Eran; Gabay, Ronnie; Rumack, Netta; Yaniv, Moshe; Dadia, Solomon; Segev, Eitan
Abstract : Background: Three-dimensional (3D) virtual surgical planning technology has advanced applications in the correction of deformities of long bones by enabling the production of 3D stereolithographic models, patient-specific instruments and surgical-guiding templates. Herein, we describe the implementation of this technology in young patients who required a corrective osteotomy for a complex 3-plane (oblique plane) lower-limb deformity. Patients and Methods: A total of 17 patients (9 males, average age 14.7 y) participated in this retrospective study. As part of preoperative planning, the patients' computerized tomographic images were imported into a post-processing software, and virtual 3D models were created by a segmentation process. Femoral and tibial models and cutting guides with locking points were designed according to the deformity correction plan. They were used for both planning and as intraoperative guides. Clinical parameters, such as blood loss and operative time were compared with a traditional surgical approach group. Results: All osteotomies in the 3D group were executed with the use intraoperative customized cutting guides which matched the preoperative planning simulation and allowed easy fixation with prechosen plates. Surgical time was 101±6.2 minutes for the 3D group and 126.4±16.1 minutes for the control group. The respective intraoperative hemoglobin blood loss was 2.1±0.2 and 2.5+0.3 g/dL. Clinical and radiographic follow-up findings showed highly satisfactory alignment of the treated extremities in all 3D intervention cases, with an average time-to-bone union (excluding 2 neurofibromatosis 1 patients) of 10.3 weeks (range 6 to 20 wk). Conclusion: The use of 3D-printed models and patient-specific cutting guides with locking points improves the clinical outcomes of osteotomies in young patients with complex bone deformities of the lower limbs. Level of Evidence: Level III.